(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
Education is the most important thing in the world. He has the power to change everything to make it better. It is well known that the only immortal thing in our lives is change and education that will definitely intensify the effort to accomplish this task. Changing the world through education means educating people with different knowledge. It also means leading people to a brighter outlook on life. According to this change, language plays a crucial role in supporting people’s lives. Language was originally used as a medium for communication. But today, language has taken an improved stage to help human life. In terms of complexity, the use of language leads people to improve and be able to compete in international life.